PERANCANGAN SISTEM INFORMASI PERSEDIAAN ATK DI KANTOR KECAMATAN BATUNUNGGALÂ BANDUNG - Muchamad Rifaldy Baitullah; Hani Hatimatunnisani (LPPM Politeknik Pajajaran ICB Bandung, 2023)
This study aims to describe the design of an office stationery inventory information system in the Batununggal District Office, Bandung City. Qualitative research methods are used by the author to provide conclusions from the formulation of the problem. Data collection techniques were carried out through literature studies, observations and interviews. The system development method uses the waterfall methods using Microsoft Visual Studio 2010 and Microsoft Access 2013 as databases. While the modeling methods uses flowmaps, context diagrams, DFD and ERD.The process of recording the inventory of office stationery that existed before was deemed ineffective, because the input process was still done one by one it was prone to errors and required a long time to input data. With the design of an easy-to-implement office stationery inventory information system , it is hoped that it can help simplify and speed up the data input process, so that monitoring of the availability of office stationery can be more effective and efficient.